Financial costs of disease burden, morbidity and mortality from priority livestock diseases in Nigeria: Disease burden and cost-benefit analysis of targeted interventions - Fadiga, M.L.; Jost, Christine; Ihedioha, J. (International Livestock Research Institute, 2011)
Nigeria’s agriculture sector generates one-third of its Gross Domestic Product (GDP) and employs two-thirds of the workforce. Its recent growth dominates Nigerian non-oil economic growth. Small-scale, semi-commercial farms, settled agricultural households and transhumant pastoralists dominate production. Livestock is the second largest agricultural sub-sector and features 16.43 million cattle, 34.69 million sheep, 55.15 million goats, 7.18 million pigs and 183.16 million poultry. These provide nutrition and food security, and a range of services including draught power for cropping activities. Poor animal productivity is widely attributed to the occurrence and endemicity of certain animal diseases. These are often unreported, unconfirmed or poorly documented. The financial losses associated with such outbreaks and costs associated with the disease burden are also rarely documented. Efforts at control of such animal diseases have yielded poor returns due to ineffective or absent control programs, insufficient inputs (such as vaccines), poor vaccination coverage due to limited vaccine supplies and constraints in field mobility and support funds, illiteracy of farmers and poor management systems. In preparation for the World Bank’s Integrated Animal and Human Health Management project for Nigeria, estimates of the economic and financial implications of high disease burden, morbidity and mortality and the costs of implementing various interventions, for all or a combination of priority diseases were required. The Government of Nigeria invited ILRI to provide such estimates for priority diseases: NCD in rural poultry flocks; PPR in sheep and goats; CBPP in cattle; ASF in pigs; and trypanosomosis in ruminants and pigs. For these diseases, and across agroecological zones, the study’s objectives were to: • assess the direct and indirect financial burden of inaction; • estimate the costs of targeted interventions; • determine the additional benefits, additional costs and net benefits associated with interventions; • evaluate of the benefit-cost ratios (BCRs) of targeted interventions; and • make recommendations on the feasibility of the targeted interventions. The study featured epidemiology and economic components. Spreadsheet-based economic modelling was effectively combined with participatory epidemiological fieldwork and analysis, and both national and international specialists contributed. Both primary and secondary data were obtained, and stakeholder consultations and expert interviews were conducted. An extensive literature review was compiled.